(untitled) (IDENTITĂȚI VS. DREPTURI. CULEGERE COMENTATĂ DE TEORIE ȘI FILOSOFIE POLITICĂ CONTEMPORANĂ, 2026)
This article analyzes David Miller’s attempt to develop a left-wing communitarian theory grounded in British socialism, nationalism, and social justice. It examines Miller’s critique of liberal individualism and his effort to reconcile community, national identity, and socialist principles without abandoning democratic values. The article also offers a critical assessment of Miller’s theoretical framework, arguing that its limited engagement with Marxist dialectics, class conflict, and global capitalism weakens its capacity to provide a comprehensive alternative to contemporary liberalism. This abstract is generated with artificial intelligence.